The Use of Google Translate in the Translation Class at English Education Study Program Pattimura University - Afiliani Afiliani; Inggrit O. Tanasale; Helena M. Rijoly (Yayasan Visi Intan Permata, 2024)
This research aimed to discover how students used Google Translate (GT), their refinement efforts, and their perceptions towards using GT in The Translation Class. The research participants were students in The Translation Class of the English Education Study Program at Pattimura University in the academic year 2022/2023. An explanatory sequential mixed method design was used in this study. The qualitative data were obtained from observation and interview and analyzed using thematic analysis. Meanwhile, the quantitative data was obtained from a questionnaire and analyzed using descriptive statistics. The results showed that students mostly used GT to facilitate translation tasks, especially for assignments, learning materials, and new vocabulary. In the classroom, GT was allowed for assignments but prohibited during exams, while students were free to use it at home. Students usually try to translate independently before using GT. They recognized the limitations of GT and made efforts to confirm and improve the translation. Despite these shortcomings, students maintained positive perceptions regarding the usefulness of GT in the Translation Classroom. These findings highlight differences in students' attitudes and perceptions towards GT and its role in translation classrooms.